Use of Human Dental Pulp and Endothelial Cell Seeded Tyrosine-Derived Polycarbonate Scaffolds for Robust in vivo Alveolar Jaw Bone Regeneration - Zhang, Weibo; Saxena, Shruti; Fakhrzadeh, Amir; Rudolph, Sara; Young, Simon; Kohn, Joachim; Yelick, Pamela C. (Frontiers in Bioengineering and Biotechnology, 2020)
The ability to effectively repair craniomaxillofacial (CMF) bone defects in a fully functional and aesthetically pleasing manner is essential to maintain physical and psychological health. Current challenges for CMF repair therapies include the facts that craniofacial bones exhibit highly distinct properties as compared to axial and appendicular bones, including their unique sizes, shapes and contours, and mechanical properties that enable the ability to support teeth and withstand the strong forces of mastication. The study described here examined the ability for tyrosine-derived polycarbonate, E1001(1K)/β-TCP scaffolds seeded with human dental pulp stem cells (hDPSCs) and human umbilical vein endothelial cells (HUVECs) to repair critical sized alveolar bone defects in an in vivo rabbit mandible defect model. Human dental pulp stem cells are uniquely suited for use in CMF repair in that they are derived from the neural crest, which naturally contributes to CMF development. E1001(1k)/β-TCP scaffolds provide tunable mechanical and biodegradation properties, and are highly porous, consisting of interconnected macro- and micropores, to promote cell infiltration and attachment throughout the construct. Human dental pulp stem cells/HUVECs seeded and acellular E1001(1k)/β-TCP constructs were implanted for one and three months, harvested and analyzed by micro-computed tomography, then demineralized, processed and sectioned for histological and immunohistochemical analyses. Our results showed that hDPSC seeded E1001(1k)/β-TCP constructs to support the formation of osteodentin-like mineralized jawbone tissue closely resembling that of natural rabbit jaw bone. Although unseeded scaffolds supported limited alveolar bone regeneration, more robust and homogeneous bone formation was observed in hDPSC/HUVEC-seeded constructs, suggesting that hDPSCs/HUVECs contributed to enhanced bone formation. Importantly, bioengineered jaw bone recapitulated the characteristic morphology of natural rabbit jaw bone, was highly vascularized, and exhibited active remodeling by the presence of osteoblasts and osteoclasts on newly formed bone surfaces. In conclusion, these results demonstrate, for the first time, that E1001(1K)/ β-TCP scaffolds pre-seeded with human hDPSCs and HUVECs contributed to enhanced bone formation in an in vivo rabbit mandible defect repair model as compared to acellular E1001(1K)/β-TCP constructs. These studies demonstrate the utility of hDPSC/HUVEC-seeded E1001(1K)/β-TCP scaffolds as a potentially superior clinically relevant therapy to repair craniomaxillofacial bone defects.